2012
DOI: 10.5527/wjn.v1.i6.184
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of dyslipidemia in chronic kidney disease: Effectiveness and safety of statins

Abstract: Several cardiovascular (CV) risk factors may explain the high rate of CV death among patients with chronic kidney disease (CKD). Among them both traditional and uremia-related risk factors are implicated and, moreover, the presence of kidney disease represents "per se" a multiplier of CV risk. Plasma lipid and lipoprotein profiles are changed in quantitative, but above all in qualitative, structural, and functional ways, and lipoprotein metabolism is influenced by the progressive loss of renal function. Statin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 0 publications
1
17
0
2
Order By: Relevance
“…Therefore, large (HDL2b and HDL2a) and medium-sized (HDL3a) particles were enriched in triacylglycerols during proteinuria in rabbits, whereas the cholesterol content of HDL subclasses remained unchanged. These data are consistent with the elevated cholesterol and triacylglycerol plasma levels frequently reported in patients with chronic kidney disease [32][33][34], particularly in patients with nephrotic syndrome; these patients are characterized by an increased apo A-I FCR [34], likewise observed in the present study. The increased catabolism of apo A-I in these patients has been associated with a loss of cholesterol acyltransferase (LCAT) activity via urine [35], and it has been also observed in other LCAT deficiencies [36].…”
Section: Discussionsupporting
confidence: 95%
“…Therefore, large (HDL2b and HDL2a) and medium-sized (HDL3a) particles were enriched in triacylglycerols during proteinuria in rabbits, whereas the cholesterol content of HDL subclasses remained unchanged. These data are consistent with the elevated cholesterol and triacylglycerol plasma levels frequently reported in patients with chronic kidney disease [32][33][34], particularly in patients with nephrotic syndrome; these patients are characterized by an increased apo A-I FCR [34], likewise observed in the present study. The increased catabolism of apo A-I in these patients has been associated with a loss of cholesterol acyltransferase (LCAT) activity via urine [35], and it has been also observed in other LCAT deficiencies [36].…”
Section: Discussionsupporting
confidence: 95%
“…Hypercholesterolemia is a well‐documented complication of CKD in dogs, with 55% of dogs with CKD having increased serum cholesterol levels 12. Dyslipidemia is a common finding in human patients with CKD of various etiologies, although this does not always result in an increased total serum cholesterol, but rather changes in the distribution of high, low, and very low density lipoproteins 13. Further studies could be indicated to determine if hypercholesterolemia is a repeatable finding in cats with CKD since information in the literature is limited for this species.…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest that CKD is a chronic inflammatory disease, as it is now recognized that rapid kidney function loss in CKD is independently associated with increased baseline levels of CRP and soluble tumor necrosis factor receptor-2 [41]. Therefore, the attenuation of the inflammatory response to renal injury on vascular structures induced by statin therapy may explain the renoprotective actions of these agents in patients with CKD [42], and suggests that inflammation represents an important target for pathogenetic interventions both in AKI and the progression of CKD. Recent evidence suggests that interleukin-1 (IL-1), a proinflammatory cytokine, plays a major role in mediating gouty arthritis inflammation [6,24,[43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%